(untitled) - Narayanasamy, P (Hoboken, NJ, 2006)
The book tells about the principles and methods of avoiding and managing posthavest diseases of fruits and vegetable products in an afficient, economical and environmentally feasible manner, allowing producers to sell safer, higher-quality produce to the public and prevent the losses associated with posthavest disease
Bảo quản sau thu hoạch
Keywords: Fruit,Vegetable,Phytopathogenic microorganisms,Trái cây,Rau cải; Postharvest diseases and injuries,Postharvest diseases and injuries,Bệnh sau thu hoạch và thương tích,Bệnh sau thu hoạch và thương tích